PERANAN ISLAMIC SOCIAL JUSTICE UNTUK MEMBANGUN KESEJAHTERAAN UMAT DI MASA PANDEMI COVID – 19 - Zakiyyah Ilma Ahmad; Lilik Rahmawati; Siti Rukmana (Jurnal Istiqro, 2022)
The purpose of this study is to examine the role of Islamic social justice during the COVID-19 pandemic, especially for the welfare of the people at large, both in the economic, health and security fields. The research in this article uses a literature study instrument which is carried out by collecting data information relating to the role of Islamic social justice during the covid-19 pandemic. Very important role is Islamic social justice which is known in the form of zakat, infaq, alms, waqf. Islamic social justice that has been carried out by philanthropic institutions on the ZISWAF instrument plays a very important role in the welfare of the people during the covid-19 pandemic in the fields of health, economy and security, although it is not comprehensive or can alleviate poverty but can improve the welfare of the community during the COVID-19 pandemic.